Membangun Karakter Mandiri pada Anak Berkebutuhan Khusus Melalui Strategi Scrum di Negara Totochan - Andhy Surya Hapsara (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
Independence is the main character that needs to be grown in children with special needs, which can be formed through inclusive education in regular schools and special education in special schools. Japan is one of countries that employs inclusive education in all schools at all levels of education. The empowerment of children with special needs in Japan is comprehensively carried out through the formation of a Scrum team that involves medical teams (physician), government, schools (teachers), universities (lecturers), and parent. The Scrum team works together continuously to assist and provide recommendations at every level of education followed by the selection of appropriate employment opportunities for children with special needs. The independent character of children with special needs is the key for them to free themselves as a burden on their family and society. Government, family, and community supports are needed to shape the independence character of children with special needs. The inclusive education system in Japan is one of the ideal models that can be adapted in Indonesia with all of its challenges, both theoretical and practical.